Differences between Rimpu Mpida and Rimpu Colo in their uses for Mbojo women in Bima Regency, Nusa Tenggara Barat, Indonesia - Hairunisah; Ilmiawan; Ahmad Afandi; Agus Herianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
This study aimed to determine the differences between rimpu mpida and rimpu colo in their use by Mbojo women in Bima Regency, Nusa Tenggara Barat (NTB), Indonesia. The research method used was the qualitative case study method. Data collection was done by using observation, interview, and documentation methods. Data analysis techniques were collection, reduction, presentation, and verification. Twelve respondents were interviewed. The results of the study found a difference. Unmarried women used rimpu mpida. In contrast, rimpu colo was used by married women. Rimpu mpida only showed the eyes, while rimpu colo showed all parts of the face. Rimpu existed when Islam first came to Bima, the specialty of rimpu mpida and rimpu colo, besides functioning as a cover for the aurat, was also a symbol that can distinguish the marital status of women in Bima. Rimpu until now was still preserved and maintained by the people of Bima. It protected women's chastity. The Bima sarongs tembe and salungka nggoli symbolized a concept. Bima provided for rimpu. Islam's entrance to Bima required women to cover their aurats, demonstrating Islamic ideals. Mbojo women in Bima adopted this practice to maintain their dignity and virtue and show loyalty to Allah.